Factors influencing seniors' acceptance of technology for ageing in place in the post-implementation stage: A literature review. (September 2019) - Tsertsidis, Antonios; Kolkowska, Ella; Hedström, Karin
Abstract: Purpose: To identify factors that influence the acceptance of technology for ageing in place by seniors in the post-implementation stage. This review is among very few that focus on acceptance in post-implementation phase. Methods: A literature review. We searched six databases (Cinahl, Medline, PsycINFO, PubMed, Science Direct, Scopus). Inclusion criteria were: 1) original and peer-reviewed research written in English, 2) Articles published in 2010–2018, 3) Empirical research papers, 4) Research in which participants are seniors aged above 60 years, 5) Research aimed at investigating factors that influence the acceptance of digital technology for ageing in place, 6) Research conducted in home environment, 7) Focus on post-implementation stage. Results: Twenty-three out of 2181 papers were included. The results show that acceptance of technology in the post-implementation stage is influenced by 36 factors, divided into six themes: concerns/problems regarding technology (technical errors, etc.), experienced positive characteristics of technology (e.g., ease of use factors, privacy implications), expected benefits of technology (e.g., increased safety, companionship, increased security, etc.), need for technology (e.g., perceived need to use), social influence (e.g., influence by peers, family or surroundings) and characteristics of older adults (e.g., past experiences/attitudes, physical environment). The articles considered different types of technology: health monitoring, ADL, safety and communication. The level of technology readiness for digital technologies supporting ageing in place in post-implementation stage is still low within the scientific literature, since only seven out of 23 articles studied mature technologies (TRL 8–9 of the technology readiness level scale). The majority of the studies were conducted in Western Europe or the US, and only two were conducted in other regions (Australia, and Taiwan). Qualitative and quantitative methods were equally used in the analysed articles. Conclusions: Acceptance of technology in the post-implementation stage is influenced by multiple factors. An interesting finding was that the seniors' views of technology change between the pre- and post-implementation stages. Some negative concerns that appeared in the pre-implementation stage appear as positive characteristics in the post-implementation stage. In the post-implementation stage, seniors realize the wide variety of benefits that technology can have on their lives. We expect that findings of this review can be utilised by academics and policy-makers for gaining insights for further research and successful implementation of technology for ageing in place.